A study of Spanish sepiolite workers. Issue 4 (April 1993) - McConnochie, K; Bevan, C; Newcombe, R G; Lyons, J P; Skidmore, J W; Wagner, J C
Abstract : BACKGROUND--Sepiolite is an absorbent clay that is used as pet litter. It forms thin crystals, which are a transition between chain and layered silicates. Inhalation studies in animals have shown no evidence of pulmonary damage. This paper reports a cross sectional study of the total work force of the largest sepiolite production plant in the world. METHODS--Two hundred and eighteen workers (210 men and eight women) were studied. Height, age, and smoking history were recorded. Chest radiographs were read according to the International Labour Office (ILO) classification by two readers. Readings were used to construct a numerical score, which was then used in statistical analyses. Forced expiratory volume in one second (FEV1) and forced vital capacity (FVC) were divided by the square of the height. Casella size selective personal samplers were used in randomly selected operatives to collect dust eight years before the rest of the study was carried out. These samples were evaluated gravimetrically. Total dust samples were examined by optical and electron microscopes. Results were analysed by bivariate linear regression, chi 2 tests, and analysis of variance. RESULTS--When allowance was made for smoking habit workers exposed to dry dust showed a significantly greater decline in FEV1 with age than workers with little exposure to dry dust. A similar pattern applied to FVC. Radiographic score showed deterioration with age but no clear differences from other variables. High concentrations of dust were found in the bagging department and also in the classifier shed. CONCLUSIONS--The major finding was that lung function deteriorated more rapidly in those who had had more exposure to dust, but there was no evidence of any accompanying radiographic change.